The effect of physical activity on the prevention and number of falls in elderly people - Danijel Božić; Milan Zelenović (University of Banja Luka, Faculty of physical education and sport, 2022)
Regular physical activity can bring significant health benefits to people of all ages, and the need for physical activity does not decrease with age, but it has been proven that it can prolong a healthier and more independent life, prevent disability and significantly contribute to improving the lives of the elderly. In addition to the fact that each type of physical activity to a certain extent improves motor skills (strength, coordination, balance, agility, ...), mental health (self-esteem, quality of life) and reduces the risk of cardiovascular and all other causes of death, regular participation in exercise promotes mobility and functional independence in adults. A fall is an event in which a participant without their own intention comes to a lying position on the ground or at a lower level. Regardless of the health status of the individual, falls are associated with insufficient movement, reduced opportunities to perform daily activities (dressing, bathing, housework, ...) and the risk of being admitted to institutions where the care of dependent persons is taken. Arthritis, depression, cognitive impairment, vision, problems with balance and unbalanced gait, decreased muscle mass, as well as excessive use of medication increase the risk of falling. The total volume and type of physical activity needed by the elderly is not very well defined. However, it can be concluded that the combination of physical activity (strength training, endurance training, exercises for the development of balance and mobility, ...) and adequate nutrition (sufficient intake of essential amino acids/protein sources) is of crucial importance for preserving physical condition, motor skills and the health status of persons of the third age, and thus also in the prevention of falls. The aim of this study is to describe and find the best training programs for the prevention of falls in the elderly.